Association Between miR-146a rs2910164 Polymorphism and Breast Cancer Susceptibility: An Updated Meta-Analysis of 9545 Cases and 10030 Controls - Moazeni-Roodi, Abdolkarim; Aftabi, Sajjad; Sarabandi, Sahel; Karami, Shima; Hashemi, Mohammad; Ghavami, Saeid; Taheri, Mohsen (MicroRNA, 2021)
Background: Several studies have reported a possible association of miR-146a rs2910164 polymorphism with Breast Cancer (BC) development. However, the correlation between this polymorphism and susceptibility to BC is under debate. The current meta-analysis was designed and performed to more conclusively evaluate the miR-146a rs2910164 polymorphism and its potential link to BC. Methods: Our team has selected eligible studies (published up to October 2, 2020) from several electronic databases, including Web of Science, PubMed, Scopus and Google Scholar. A total number of 9,545 BC cases and 10,030 controls extracted from 26 eligible articles were included in this study. We utilized pooled Odds Ratios (ORs) as well as 95% confidence intervals (95% CIs) under five genetic models for quantitative estimation of any possible association between miR-146a rs2910164 polymorphism and BC. Results: Based on this meta-analysis, our findings suggest that there is no significant association between miR-146a rs2910164 polymorphism and BC risk. However, stratified analysis revealed that the rs2910164 polymorphism significantly increased the risk of BC in hospital-based studies using the homozygous genetic model (OR=1.37, 95%CI=1.01-1.86, p=0.043, CC vs. GG). Neither Asian nor Caucasian populations showed any significant association between rs2910164 polymorphism and BC susceptibility. Conclusion: In summary, our findings suggest that BC development is not associated with miR-146a rs2910164 polymorphism. However, larger ingenious future investigations might be needed for a more precise estimation of any association between miR-146a rs2910164 polymorphism and BC.
Keywords: mir-146a